Tension stiffening model for lightly confined reinforced concrete elements. Issue 7 (4th April 2021) - Menegon, Scott J; Wilson, John L; Lam, Nelson TK; Gad, Emad F
Abstract : Reinforced concrete (RC) walls subject to in-plane lateral loads are essentially subject to axial compression and tension forces in the respective end regions of the wall. The tension forces initially result in elastic tensile stresses in both the concrete and longitudinal reinforcement. Cracking occurs after the maximum tensile stress of the concrete has been exceeded and results in the reinforcement providing the sole tensile resistance at each crack location. The mechanical interlock between the reinforcement and concrete means that a portion of the tensile stress in the reinforcement at each crack is transferred back into the concrete between adjacent cracks. This mechanism stiffens the concrete in tension and is referred to as tension stiffening. This paper presents a generalised tension stiffening model developed for limited ductile (i.e. lightly confined) RC walls. However, it is also applicable for lightly confined RC elements generally. The model was validated against 14 boundary element prism specimens subject to cyclic loading, with very good correlation observed between the theoretical model and the experimental results. This model can easily be adopted into a sectional analysis procedure to account for tension stiffening in both the elastic and inelastic regions of response in an RC wall.